Advances and Slowdowns in Carbon Capture and Storage Technology Development - Aurora D'Aprile (Fondazione Eni Enrico Mattei (FEEM), 2016)
With the long term goal of holding the increase in the global average temperature to well below 2°C and "to pursue efforts to limit the temperature increase to 1.5°C", the Paris Agreement puts renewed attention on the portfolio of technologies needed to achieve consistent emission reductions and reach "a balance between anthropogenic emissions by sources and removals by sinks” in the second half of this century. Carbon capture and storage (CCS) technology, after having been hailed as a promising mitigation option around a decade ago, is undergoing a gruelling path to stay on top of the expectations. The opportunities and constraints in deploying large-scale carbon capture and storage systems are of the utmost actuality, as the technology promises to get rid of up to 90% of the most common greenhouse gases produced in industrial and energy plants before they reach the atmosphere (or even to achieve “negative” emissions, if combined with biomass). Despite potential benefits, CCS development and deployment proceeded at a far slower rate than what was expected and are struggling to emerge as a sound low-carbon choice for governments and investors. Based on recent existing literature, this reflection explores the main progress and deadlocks in CCS's difficult path.
Keywords: Q42; Q55; Q58; 330; Climate Change; Carbon Sequestration; CCS; Carbon Mitigation; Low-carbon Technology